2020
DOI: 10.14309/ajg.0000000000000926
|View full text |Cite
|
Sign up to set email alerts
|

Fendrix vs Engerix-B for Primo-Vaccination Against Hepatitis B Infection in Patients With Inflammatory Bowel Disease: A Randomized Clinical Trial

Abstract: INTRODUCTION: To compare Engerix-B and Fendrix hepatitis B virus for primo vaccination in inflammatory bowel disease (IBD). METHODS: Patients with IBD were randomized 1:1 to receive Engerix-B double dose or Fendrix single dose at months 0, 1, 2, and 6. Anti-HBs titers were measured 2 months after the third and fourth doses. Response to vaccination was defined as anti-HBs ≥100 UI/L. Anti-HBs titers were measured 2 months after the third and fourth doses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 27 publications
1
25
0
1
Order By: Relevance
“… 52 A recent RCT from Chaparro et al found a 4‐dose schedule was more effective than a 3‐dose regimen with significantly higher response rates for Hepatitis B vaccination in patients with IBD. As seen in other studies older age and treatment with immunomodulators or anti‐TNFs impaired response to vaccination 53 …”
Section: Do Ibd Therapies Reduce Vaccine Responses In Patients With Ibd?supporting
confidence: 74%
See 2 more Smart Citations
“… 52 A recent RCT from Chaparro et al found a 4‐dose schedule was more effective than a 3‐dose regimen with significantly higher response rates for Hepatitis B vaccination in patients with IBD. As seen in other studies older age and treatment with immunomodulators or anti‐TNFs impaired response to vaccination 53 …”
Section: Do Ibd Therapies Reduce Vaccine Responses In Patients With Ibd?supporting
confidence: 74%
“…As seen in other studies older age and treatment with immunomodulators or anti-TNFs impaired response to vaccination. 53 ECCO guidelines recommend all IBD patients receive an accelerated vaccination schedule using a double-dose protocol, whilst the ACG guidelines recommend the standard vaccination schedule. 5,19 Once further data are available on response rates in patients with IBD to the COVID-19 vaccines the use of accelerated or double-dose vaccine schedules for sub-cohorts of patient with IBD that have impaired response to the vaccine may be an option.…”
Section: Hepatitis B Vaccinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Standard doses of 10–20 μg (as recommended by manufacturer) were used for vaccination in 13 studies 7,17–20,22–24,28,31,33,35,36 . Three studies used the double dose (40 μg) 26,27,30 and two studies compared the double dose with standard dose 21,25 . The exact dose of vaccine administered was not mentioned in three studies 29,32,34 …”
Section: Resultsmentioning
confidence: 99%
“…Loras et al [ 59 ] used the same scheme for the vaccination of IBD patients under anti-TNF treatment and found a 57% response rate. A study by Chaparro et al [ 68 ] compared the double-dose Engerix-B ® vaccine given in a four-dose schedule (0-1-2-6 mo intervals) with the single-dose Fendrix ® given in the same intervals. The two vaccines demonstrated equivalent effectiveness rates but the four-dose protocol exhibited enhanced efficacy (range: 68%-75%) in achieving anti-HBs titers above 100 IU/mL.…”
Section: Management Of Hbv Infection In Patients With Ibdmentioning
confidence: 99%